In vitro anti-ageing activities of ethanolic extracts from Pink rambutan (Nephelium lappaceum Linn.) for skin applications - Korawinwich Boonpisuttinant; Ratakorn Srisuttee; Heng Yen Khong; Romchat Chutoprapat; Warintorn Ruksiriwanich; Sarinporn Udompong; Wirinda Chompoo; Rattiya Boonbai; Rattikarl Rakkaew; Jinapa Sangsee; Ketsani Sriprasert; Waraporn Malilas (Saudi Pharmaceutical Journal, 2023)
) on human skin fibroblasts by the RT-PCR method, which were similar to standards ʟ-ascorbic acid and resveratrol, respectively. This study suggests that the PR-R-Sox and PR-Y-Sox extracts can be further developed as natural anti-ageing agents for whitening and anti-wrinkle in the cosmetics, cosmeceutical, and pharmaceutical industries.
Keywords: Phytochemicals and Antioxidant Activities; melanin and skin pigmentation; Skin Protection and Aging